ANIMASI DAN PERMAINAN EDS (ELEMENTARY DENTAL SCHOOL) SEBAGAI METODE INTERAKTIF PENDIDIKAN KESEHATAN GIGI DAN MULUT SISWA SEKOLAH DASAR - Prasonto, Djuned; Prihastari, Lisa; Ronal, Ahmad (Jurnal BALIRESO, 2019)
Early dental caries prevention in this case self-care oral cultivation needs to be done primarilyin primary school-aged children. Indonesians are people who have not considered oral healthsince their early years. Dental and oral health education programs with aspects that onlyemphasize the realm of knowledge is not significant enough to change the paradigm in societyand reduce the number of caries. Elementary dental school (EDS) using appreciative inquiryapproach develops positive change concept which is a new discourse in the world of healthpromotion.With the appreciative inquiry approach, the positive core that will be used as amedium of transformation builds awareness and forms a healthy paradigm in children. Theprogram seeks to raise awareness of maintaining oral hygiene through the stages of providingdance knowledge through animation and games by integrating school and home environmentsthrough the participation of teachers and parents.The results of the implementation of EDSprogram showed significant changes of knowledge in children especially seen from theincrease of post test value compared to the pre test value which experienced an increase of35.3%.